Learning computer programming through game playing - Bachu, Eshwar; Bernard, Margaret (My University, 2012)
In this paper we present an approach for teaching and learning Computer Programming through game playing. This activity is intended to complement traditional teaching of concepts. The focus is on building program comprehension rather than program generation. In playing the game, students improve their ability to read and understand a program written in a specific language and to follow the logic in a program. They build speed in comprehension, as is required in learning any language. To win the game, students have to play certain steps repeatedly, using different strategies, and with time constraints. This repetitiveness reinforces learning. Once they master the basic elements of a program, they will experience less frustration in coding solutions for more challenging problems. The preliminary results with students using this gaming activity are encouraging.
Keywords: Pascal programming; Pascal shopper; Computer games